The Habsy and Burdah Training to Enhance Children's Skills in Terawan Village by Local Community Service Program of IAIN Palangka Raya - Citra, Yulia; Daniel, Daniel Wahyu Ramadani; Munawir, Munawir; laily, Nur Laily Mufidah; Yunia, Siti Maria Noorlaila Yunia Bekhti; Ali, Ali Iskandar Zurkarnain (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This study examines the implementation of community service activities teaching traditional religious arts (Habsy and Burdah) to children in Terawan Village. It aims to enhance children's skills, preserve cultural heritage, and empower the community. Method: Qualitative descriptive research using Field Research methodology is employed. Data is collected through observation, interviews, and documentation, then analyzed thematically. Practical Applications: The research informs community service organizations, educators, and policymakers about the effectiveness of engaging children in traditional arts. It highlights the significance of cultural preservation and community involvement, suggesting potential for similar programs elsewhere. Conclusion: This research demonstrates the positive impact of traditional arts activities on children's development and community cohesion. It emphasizes the importance of cultural preservation and community engagement, advocating for broader implementation of such initiatives.